Understanding women's experiences and perceptions of sexuality within the framework of menopause - Uygunöz, Semiha Başak (İstanbul Bilgi Üniversitesi, 2019)
Menopause bas been a topic that has been discussed in various fıelds for ages and it has been thought that it can affect women in many ways. What would happen in their sexual lives, when they go through menopause becomes an issue that women often consider. Although studies in the field of medicine have indicated that sexuali1y is adversely affected by menopause and increasing age, more feministminded researchers have attempted to show through qualitative methods that positive changes also can be experienced by the women by focusing on their narratives. TI1e lack of qualitative studies on menopause and sexuality in Turkey is remarkable. Therefore, this study aimed to deeply examine the perception and experiences about sexuality of Turkish women in the context of their experiences and meanings attributed to menopause. For this purpose, semi-structured, face-toface interviews were conducted by the researcher of this thesis with 8 heterosexual oriented women between the ages of 45 and 60. These interviews were analyzed using the MAXODA program with lnterpretative Phenomenological Analysis (IPA) and 5 superordinate themes were obtained: a) effects of menopause on women. b) making sense of menopause. c) changes in sexual life, d) making sense of sexuality and e) strategies of coping with menopausal effects, along with 13 subordinate themes. The resu1ts were discussed within the framework of previous research and theories, and; clinical implications from the current research were indicated.

Menopoz çok eski dönemlerden bu yana değişik alanlarda tartışılan ve kadınları birçok yönden etkileyebileceği düşünülen bir konu olmuştur. Menopozla beraber cinsel hayatlarında neler olacağı ise kadınların üzerine sıkça düşündüğü bir mesele haline gelmiştir. Özellikle tıp alanında yapılan çalışmalar. cinselliğin menopoz ve artan yaşla beraber olumsuz yönde etkilendiğine dair bulgular sunsa da daha feminist görüşlü kuramcı araştırmacılar olumlu yönde değişimler de yaşanabileceğini. ağırlıklı olarak kullandıkları niteliksel araştırmalarla, kadınların anlatılarına yer vererek göstermeye çalışmışlardır. Türkiye’de ise menopoz ve cinselliğe dair yapılan niteliksel çalışmaların azlığı göze çarpmaktadır. Bu nedenle, bu çalışma, menopozdaki Türk kadınlarının cinsellikle ilgili algı ve deneyimlerin????? menopoza atfettikleri anlamlar ve deneyimler çerçevesinde derinlemesine incelemeyi hedeflemiştir. Bu amaç doğrultusunda, tezin araştırmacısı tarafından, 45 ile 60 yaş arasında, heteroseksüel yönelimli 8 kadın ile yarı yapılandırılmış yüz yüze görüşmeler yapılmıştır. Bu görüşmeler, Yorumlayıcı Fenomenolojik Analiz yöntemi ile MAXQDA programından faydalanılarak analiz edilmiş, 5 ana tema ve bunlara bağlı olarak 13 alt tema elde edilmiştir: a) menopozun kadınlar üzerindeki etkileri, b) menopozu anlamlandırma, c) cinsel yaşamdaki değişimler, d) cinselliği anlamlandırma, e) menopoz.al etkilerle baş etme stratejileri. Sonuçlar, daha önce yapıları araştırmalar ve teoriler çerçevesinde tartışılmış: araştırmadan ulaşılan klinik çıkarımlar belirtilmiştir.
Kadınların cinsellik deneyimlerini ve algılarını menopoz çerçevesinde anlamak